GAMIFICATION IN TRAINING OF SOCIAL WORKERS - Vasylieva, Maryna; Romanova, Inna; Sheplyakova, Irina (Educological discourse, 2020)
The article analyzes the meaning of the concept of "gamification". It is determined that since 2011 the number of specialized conferences, books and research on the topic of gamification has increased, but its content is interpreted differently by scientists: both as a process and as a set of techniques or techniques. It is characterized that gamification in education is used in two meanings: in a broad sense - the game shell (attributes, techniques, elements) is used without the use of ICT; in the narrow - gamification is based on the use of ICT (video games, specialized programs, etc.). The purpose of using gamification at higher education institutions in experimental research is clarified. The main components of gamification are identified. It has been found that scientists warn against mechanistic using of marketing methods in education. Experiences of using gamification in the training of social workers (Concordia University (Portland, USA) and the Center for Applied Social Research RTIM (Australia)) are analyzed. The most common practices are identified: online courses (MOOK) in the social field, trainings, gamification support platforms; 3D virtual environment. It has been found that gamification has not yet become widespread in the training of social workers. It is determined that the results of empirical studies of the effectiveness of gamification for the quality of training of social workers are different and reveal complications of technical, psychological and pedagogical nature. The factors that limit the introduction of gamification in the educational process are described. The possibilities of using gamification in the training of social workers in higher education institutions are generalized. It is determined that the choice of types and methods of implementation of game elements should be determined by the teacher depending on the general objectives of the discipline, ensuring the implementation of the educational program, and comply with the Standard for training a specialist in the social field. Increasing demand for distance learning services will expand the search for ways to use gamification in the training of social workers. It is planned to develop a general game scenario for a discipline in the LMS Moodle environment for distance learning of future social workers.